Strategi Komunikasi Pemasaran dalam Mengembangkan Usaha Wedding Organizer di Masa New Normal: Study Kasus Ivora Organizer - Nasution, Fildzah Gassani; Susanti, Neila; Abidin, Syahrul (Communication & Social Media, 2022)
As a result of the Covid-19 pandemic, wedding organizers face the problem of declining income turnover which makes them have to have a way to develop their business in the new normal period through marketing communication strategies. The purpose of this study is to find out how the marketing communication strategy in developing the Wedding Organizer business in the new normal period in the Ivora Organizer case study. The type of research used in this research is descriptive qualitative research. The results of this study indicate that Ivora Organizer's marketing communication strategy activities use Instagram social media during the new normal period to develop their business. The conclusion of this research is that Ivora Organizer's marketing communication strategy in developing a wedding organizer business in the new normal is going very well, as can be seen from Ivora Organizer who already has his own place of business.